Injectable hydroxyapatite - b-tricalcium phosphate – calcium sulphate biocement - Wan Khartini Wan Khodir,; Roslinda Shamsudin,; Abdul Razak Daud,; Yusof Abdullah, (Universiti Kebangsaan Malaysia, 2005)
Injectable biocement as bone substitute material for filling in parts of defect bone and capable of setting itself in the body was produced based on a mixture of 40-50% hydroxyapatite, 10-20% b-tricalcium phosphate and 40-60% calcium sulphate dehydrate. Two different liquids were used for the preparation of the biocements, namely deionised water and phosphate buffer solution (pH 7). The influences of powder composition, weight ratio of liquid-to-powder and powder particle size on the injectability; setting time and compressive strength of the cement were reported.